Circular Economy and Climate Change in Ukraine: A Statistical Analysis of Emissions, Waste, and Environmental Investments - Hrynchak N. А.; Kobylynska Т. V.; Motuzka, O. M. (Statistics of Ukraine, 2025)
This article presents a statistical analysis of the relationship between the development of the circular economy and climate change in Ukraine during the period 2010–2024. The circular economy, as an alternative model of production and consumption, is based on principles of resource efficiency, waste minimization, and the maximization of reuse and recycling. The paper analyzes key statistical indicators, including atmospheric emissions, waste generation and treatment, and the dynamics of environmental protection investments. The findings reveal a relative decoupling between GDP growth and emissions levels, suggesting some progress in energy modernization and industrial efficiency. However, these improvements are largely attributed to reduced industrial activity caused by the ongoing war rather than systematic ecological reforms. Despite isolated efforts to implement circular solutions, the overall level of circularity in Ukraine’s economy remains low. The analysis highlights a significant gap between current expenditures and the capital investments needed for effective environmental protection. Landfilling continues to dominate waste management practices, contradicting the core principles of circularity. The article emphasizes that Ukraine’s post-war reconstruction presents a unique opportunity for deep ecological transformation. The integration of circular economy principles should be a key element of the country’s long-term sustainable development strategy. This includes enhancing the legal and institutional framework, building waste processing infrastructure, fostering green innovation, and cultivating environmental awareness across all sectors of society. Further research is needed to model the impact of circular measures on greenhouse gas reduction, assess the cost-effectiveness of investments in green infrastructure, and explore the recycling potential of war-related construction and demolition debris. The circular economy is thus positioned as a strategic tool for achieving environmental and economic resilience amid ongoing climate and socio-economic challenges.